Pengukuran Beban Kerja Karyawan Pada Lantai Produksi Dengan Metode Work Sampling (Studi Kasus PT. Teluk Luas) - Ernita; Riko Ervil; Karissa Handayani (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2019)
PT Teluk Luas is a local investment company (PMDN) engaged in Processing Crumb Rubber SIR 10 and SIR 20, with 80% export oriented and 20% local oriented. In general, working process at PT. Teluk Luas is still manual such as dismantling the cargo of rubber from the truck to the raw material warehouse, lifting the rubber from one work station to the next station (pressing station), cutting the rubber and drying the rubber mill to the drying area that has been provided. To prevent the occurrence of work overload, it is necessary to measure the workload of employees who do the work by using their physical energy. Work sampling is a technique for holding a large number of observations on the work activities of workers. Observation of work activities for time intervals taken randomly to one or more workers and then record whether the worker is working or unemployed. Measurement of employee loads by work sampling method to calculate standard time, standard production, and work load. From result of data processing, standard time needed to produce one unit of product at pressing station is 1.68 minutes. Working burden on the press is 77.78%. Percentage earning more than 75% is too heavy for workers in carrying out work activities.